2007
DOI: 10.1523/jneurosci.2279-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

A TAT–DEF–Elk-1 Peptide Regulates the Cytonuclear Trafficking of Elk-1 and Controls Cytoskeleton Dynamics

Abstract: The transcription factor Elk-1 plays a key role in cell differentiation, proliferation and apoptosis. This role is thought to arise from its phosphorylation by activated extracellular signal-regulated kinases (ERKs), a critical posttranslational event for the transcriptional activity of the ternary complex composed of Elk-1 and a dimer of serum response factor (SRF) at the serum response element (SRE) regulatory site of transcription. In addition to its nuclear localization, Elk-1 is found in the dendrites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 34 publications
6
62
1
Order By: Relevance
“…In contrast, PC12 cells overexpressing a constitutively nuclear mutant of Elk-1 show a facilitation of neuronal differentiation (Vanhoutte et al, 2001;Salinas et al, 2004). More recently, using the TDE peptide or a dominant-negative version of Elk-1 in primary striatal cultured cells, we found an inhibition of spontaneous dendritic outgrowth as well as cytoskeleton dynamics (Lavaur et al, 2007). As described previously (Shen et al, 2008), we found a global increase of spine density in NAcc shell MSNs after a chronic treatment with cocaine.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In contrast, PC12 cells overexpressing a constitutively nuclear mutant of Elk-1 show a facilitation of neuronal differentiation (Vanhoutte et al, 2001;Salinas et al, 2004). More recently, using the TDE peptide or a dominant-negative version of Elk-1 in primary striatal cultured cells, we found an inhibition of spontaneous dendritic outgrowth as well as cytoskeleton dynamics (Lavaur et al, 2007). As described previously (Shen et al, 2008), we found a global increase of spine density in NAcc shell MSNs after a chronic treatment with cocaine.…”
Section: Discussionsupporting
confidence: 78%
“…8). In cultured striatal neurons, the TDE is a selective inhibitor of ERK-dependent Elk-1 phosphorylation induced by glutamate in vitro (Lavaur et al, 2007). One important constraint of our in vivo study was to determine whether ERK-dependent phosphorylation of Elk-1 and MSK-1 occurred in the same striatal population in response to cocaine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations